2013
DOI: 10.1371/journal.pone.0074950
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancers from Distinct Ancestral Populations Show Variations in BRAF Mutation Frequency

Abstract: It has been demonstrated for some cancers that the frequency of somatic oncogenic mutations may vary in ancestral populations. To determine whether key driver alterations might occur at different frequencies in colorectal cancer, we applied a high-throughput genotyping platform (OncoMap) to query 385 mutations across 33 known cancer genes in colorectal cancer DNA from 83 Asian, 149 Black and 195 White patients. We found that Asian patients had fewer canonical oncogenic mutations in the genes tested (60% vs Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
4
21
1
Order By: Relevance
“…The difference could not be explained by the methodology, as the same method was used and similar overall BRAF mutation rates have been reported in other Asian populations 26 27. Considering that CRCs in Asians may have a lower BRAF mutation rate than those in white patients,28 EOCRCs in Taiwan are particularly prone to this molecular alteration.…”
Section: Discussionmentioning
confidence: 62%
“…The difference could not be explained by the methodology, as the same method was used and similar overall BRAF mutation rates have been reported in other Asian populations 26 27. Considering that CRCs in Asians may have a lower BRAF mutation rate than those in white patients,28 EOCRCs in Taiwan are particularly prone to this molecular alteration.…”
Section: Discussionmentioning
confidence: 62%
“…The finding is consistent with previous reports from Taiwan (3.8–5.8%) and similar to the reports of other Asian countries (1.7–9%) . In an ethnicity‐based study by Hanna MC et al ., the frequency of BRAF mutations in CRCs has been shown to be significantly different between Asian (4%) and Caucasian populations (17%), while mutations in other cancer genes such as APC , CTNNB1 , KRAS , NRAS , PIK3CA and TP53 show no difference . The BRAF mutation has been proposed to be the earliest event in the microsatellite instability pathway of colon cancer carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] In an ethnicity-based study by Hanna MC et al, the frequency of BRAF mutations in CRCs has been shown to be significantly different between Asian (4%) and Caucasian populations (17%), while mutations in other cancer genes such as APC, CTNNB1, KRAS, NRAS, PIK3CA and TP53 show no difference. 38 The BRAF mutation has been proposed to be the earliest event in the microsatellite instability pathway of colon cancer carcinogenesis. 39 The lower BRAF mutation rates indicated that colorectal cancers are involved infrequently in this pathway among Asians.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted on colorectal cancer, it was discovered that a lower mutational load appeared in Asians compared to African-Americans and Caucasians (60% vs. 79 & 77%) upon investigation of 385 mutations across 33 known cancer genes. BRAF mutations were more prevalent in Caucasians, with the highest frequency observed for the BRAF V600E mutation (130). …”
Section: Metabolic Gene Mutations As Differential Predictors Of Cancementioning
confidence: 99%